2022
DOI: 10.3389/fcvm.2022.858909
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ Mediates the Cardioprotective Roles of Danlou Tablet After Acute Myocardial Ischemia-Reperfusion Injury

Abstract: Ischemic heart disease is one of the biggest threats to human life in the world. Reperfusion therapy is an effective strategy to reduce infarct size and ischemic injury. However, reperfusion process may cause secondary myocardial injury which is defined as ischemia-reperfusion injury (IRI). Exploring potential therapeutic strategy to attenuate IRI is extremely important. Danlou tablet (Dan), a Chinese herbal compound consisting of ten herbs, has been identified to be protective for the heart. However, the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Thus, proper and effective treatments for DCM are in urgent demand. Dan has been reported to have cardioprotective effects in multiple cardiovascular diseases, such as atherosclerosis, myocardial ischemia-reperfusion injury [ 17 , 19 ], etc. However, whether Dan confers protection against DCM is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, proper and effective treatments for DCM are in urgent demand. Dan has been reported to have cardioprotective effects in multiple cardiovascular diseases, such as atherosclerosis, myocardial ischemia-reperfusion injury [ 17 , 19 ], etc. However, whether Dan confers protection against DCM is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Dan protected against myocardial reperfusion injury by regulating endothelial and inducible nitric oxide levels [ 36 ]. Furthermore, a recent study reported that the administration of Dan reduced acute myocardial injury and cardiomyocyte apoptosis by activating PPARγ [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations